Let’s Explore: Predictive Ability of Urinalysis for Diagnosis of Urinary Tract Infection in CKD Patients (Journal of Chittagong Medical College Teachers' Association, 2020)
Background: Immuno-compromised Chronic Kidney Disease (CKD) patients are more vulnerable to infection. Among all infections, Urinary Tract Infection (UTI) is the main culprit of increased morbidity and mortality. So to combat this and to retard disease progression, control of UTI is a prime concern for this group of patients. Quantitative urine culture is the 'gold standard' method for definitive diagnosis of urinary-tract infections, but it is intensively time and labor consuming.  For initiating early empirical treatment even in absence of localizing symptoms, the same day result is very helpful. Culture may lead to delaying of diagnosis. The microscopy of urine thus may be an essential tool for the diagnosis of patients with urinary tract infections. The aim of this study was to evaluate the diagnostic performance of the common urinalysis parameters in comparison to urine culture as the reference method.Materials and methods: We evaluated 1000 urine samples, submitted for urine analysis and culture admitted in Nephrology ward, Chattogram Medical College Hospital, a large tertiary care hospital for one year from 1st January 2017 to 31st December 2017. A cross-sectional study was done. Different Cut-off values were determined from different studies obtained by comparing the results with urine cultures. The test characteristics by the sensitivity, specificity, PPV and NPV were calculated for bacteria and White Blood Cells (WBCs) Red Blood Cells (RBC) glucose in urine and albuminuria. A practical diagnostic threshold of bacteriuria was determined. The diagnostic performance of culture was compared with different parameters of urinalysis.Results: Among the 1000 urine specimens submitted for culture, 618 cultures (61.8%) were positive, and 382 were (38.2%) negative. The cut-off value for pyuria was determined ³10 pus cell/HPF and compared for bacteriuria (Sensitivity: 69%, specificity: 36%, PPV: 64%, NPV: 42%) and presence of sugar and albumin in urine were found associated significantly with culture positivity at 95% CI (Sensitivity: 15%, specificity: 90%, PPV: 70%, NPP: 39% and sensitivity: 97%, specificity: 6%, PPV: 62%, NPP: 59%) respectively. And association between RBC and pus cell in urine microscopy was significant.Conclusions: UTI is a common infection in CKD patients with high incidence. Though culture is the gold standard, but urinalysis by cell count for pyuria, dipsticks for the presence of sugar or albumin may be helpful to diagnose UTI. The association of these all characteristics with growth in culture was statistically significant.JCMCTA 2020 ; 31 (1) : 26-30